지역사회 경증치매노인의 행동심리증상과 가족의 부양스트레스 및 자기효능감 - 임동영(Dong-Young Lim); 장현정(Hyun-Jung Jang) (한국콘텐츠학회 논문지, 19(4), 2019)
The purpose of this study is to provide a basic data for reducing care-giving stress of family members of the elderly with mild dementia by determining the relationship between the behavioral and psychological symptoms of the elderly with dementia and their family members' care-giving stress and self-efficacy. The descriptive statistics, t-test, and ANOVA were used for analysis in order to investigate the relationship. The behavioral and psychological symptoms of the elderly with mild dementia and their family members' care-giving stress had a positive correlation (r=.655, p<.001), and as their family members' care-giving stress and the members' self-efficacy had a negative correlation (r=-.334, p<.001). Based on the result of this study, it is necessary to reduce the care-giving stress of family members of the elderly with mild dementia and improve the self-efficacy of family members by developing proper measures to cope with the behavioral and psychological symptoms of the elderly with mild dementia. 본 연구는 경증치매노인의 행동심리증상과 가족의 부양스트레스 및 자기효능감의 관계를 파악함으로써 치매노인 가족의 부양스트레스를 감소시키는데 기초자료를 제공하기 위함이다. 이에 따른 관계를 규명하기 위한 분석은 기술통계, t-test, ANOVA를 이용하였다. 경증치매노인의 행동심리증상에 대한 가족의 부양스트레스와 자기효능감에 대해 알아본 결과, 치매노인의 행동심리증상과 가족의 부양스트레스는 양의 상관관계 (r=.655, p<.001), 치매노인 가족의 부양스트레스와 자기효능감은 음의 상관관계(r=-.334, p<.001)가 있었다. 본 연구결과를 토대로 경증치매노인의 행동심리증상에 대한 적절한 대처법 개발을 통해 지역사회 경증치매노인 가족의 부양스트레스를 감소시키고 자기효능감을 향상시키기 위한 방안이 필요할 것으로 사료된다.